The effect of the Osborne model in the acquisition of concepts For second-grade students In Islamic education - زين العابدين شهباز انتصار (Al-Adab Journal, 2018)
Search goal The current research aims at identifying the effect of the Osborne model on the acquisition of concepts by second grade students in Islamic education. Search procedures The researcher used the Osborne model, which was applied to the experimental group, and the traditional method of control group. Cavat interrogated them in the IQ test. And the age of time, and degrees of Islamic education for the previous year, and the achievement of Dasi father and mother. The researcher used the T-test for two independent samples to analyze the data, and used a standard tool to measure the performance based on the correction criteria prepared by the researcher. search result The result of the search exceeded the experimental group on the control. The researcher recommended the adoption of the Osborne model in the lesson of Islamic education. She proposed a similar study for the current study at other stages of the middle school.